Numerical Evaluation of a Light-Gas Gun Facility for Impact Test. (18th August 2014) - Rahner, C.; Al-Qureshi, H. A.; Stainer, D.; Hotza, D.; Fredel, M. C.
Abstract : Experimental tests which match the application conditions might be used to properly evaluate materials for specific applications. High velocity impacts can be simulated using light-gas gun facilities, which come in different types and complexities. In this work different setups for a one-stage light-gas gun facility have been numerically analyzed in order to evaluate their suitability for testing materials and composites used as armor protection. A maximal barrel length of 6 m and a maximal reservoir pressure of a standard industrial gas bottle (20 MPa) were chosen as limitations. The numerical predictions show that it is not possible to accelerate the projectile directly to the desired velocity with nitrogen, helium, or hydrogen as propellant gas. When using a sabot corresponding to a higher bore diameter, the necessary velocity is achievable with helium and hydrogen gases.